Pengaruh Modal Kerja Terhadap Net Profit Margin pada Industri Makanan dan Minuman yang Terdaftar di BEI - Karunia Putri Augustina Dwi Anggiyani; Leni Nur Pratiwi; Banter Laksana (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The aims of this research are to analyze the effect of Working Capital Turnover, Inventory Turnover, Cash Turnover, Receivables Turnover, and Short-term Debt to Net Profit Margin (NPM) at food and beverage industry listed on BEI (Indonesia Stock Exchange) Period 2017-2019. This research is using purposive sampling method and obtained a sample of 6 companies. The analysis used to determine the effect of Working Capital Turnover, Inventory Turnover, Cash Turnover, Receivable Turnover, and Short-Term Debt on Net Profit Margin (NPM) is a statistical analysis with using the help of SPSS 22.0 software. The results of this study indicate that the Working Capital Turnover, Inventory Turnover, Cash Turnover, Receivable Turnover and Short Term Debt variables simultaneously have a significant effect on Net Profit Margin (NPM). Working Capital Turnover, Inventory Turnover and Short-term Debt partially have a negative effect on NPM. Receivables turnover has a positive effect on NPM. whereas, cash turnover does cash turnover does not have an effect on NPM.